Experimental Investigation of Thermal Conductivity and Electrical Conductivity of Al2O3 Nanofluid in Water - Ethylene Glycol Mixture for Proton Exchange Membrane Fuel Cell Application - Irnie, Zakaria; Azmi, W. H.; W. A. N., W. Mohamed; R., Mamat; G., Najafi (Elsevier, 2015)
Nanofluid is an alternative promising cooling liquid with superior performance characteristic compared to conventional cooling liquid for Proton Exchange Membrane fuel cell (PEMFC). In this paper, new findings on ratio of thermal conductivities and electrical conductivities of nanofluids inwater: ethylene glycol (EG) mixtures are established. Thermal conductivities and electrical conductivities of base fluids which are water: EG mixtures with concentration ranging from 0 % ethylene glycol up to 100 % ethylene glycol were measured. These base fluids are then dispersed with Al2O3 at 0.1, 0.3 and 0.5 % of volume concentration and thermal conductivities and electrical conductivities are then measured at temperature of 20 °C. The result demonstrates that thermal conductivities reduced as the EG content percentage increases in the water: EG mixture. Thermal conductivities for 0.5 % volume concentration of Al2O3 is 0.6478 W/m.K and 0.2816 W/m.K for 0 and 100 % EG content in water: EG mixture. However, at a specific EG percentage, thermal conductivities also increased as a function of volume concentration. Electrical conductivities measured in 0.1, 0.3 and 0.5 % volume concentration of Al2O3 in base fluid also observed to decrease as the EG concentration increased even though the base fluids’ electrical conductivity behave differently. Thermo-electrical conductivity ratio (TEC) has also been established based on both thermal and electrical conductivity findings.